Effect of Novel Melanocortin Type 2 Receptor Antagonists on the Corticosterone Response to ACTH in the Neonatal Rat Adrenal Gland In Vivo and In Vitro - Nensey, Nasha K.; Bodager, Jonathan; Gehrand, Ashley L.; Raff, Hershel (Frontiers in Endocrinology, 2016)
Stress-induced increases in neonatal corticosterone demonstrate a unique shift from ACTH-independence to ACTH-dependence between post-natal day two (PD2) and eight (PD8) in newborn rats. This shift could be due to binding of a bioactive, non-immunoreactive, plasma ligand to the adrenocortical MC2R (ACTH receptor). A potent MC2R antagonist would be useful to evaluate this phenomenon in the neonate. Therefore, we investigated the acute corticosterone response to ACTH(1-39) injection in rat pups pretreated with newly developed MC2R antagonists (GPS1573 and GPS1574), which have not been tested in vivo. The doses used in vivo were based on their in vitro potency, with GP1573 being more potent than GPS1574. GPS1573 (PD2 and PD8), GPS1574 (PD2 only), or vehicle were injected intraperitoneally (ip) 10 min before baseline sampling. Then, 0.001 mg/kg of ACTH(1-39) was injected ip and subsequent blood samples obtained for the measurement of plasma corticosterone. Pretreatment of PD2 pups with GPS1573 demonstrated augmentation, rather than inhibition, of the corticosterone response to ACTH. In PD8 pups, pretreatment with 0.1 mg/kg GPS1573, but not 4 mg/kg, augmented the corticosterone response to ACTH. Pretreatment with GPS1574 attenuated the plasma corticosterone response to ACTH at 30 min in PD2 pups. The activity of these two compounds in vivo do not match their potency in vitro, with GPS1573 leading to a small augmentation of the corticosterone response to ACTH in vivo, while GPS1574 resulted in inhibition.